The Myth of Egmont as an Example of the Construction of Historical Understanding (KULT_online, 2011)
Egmont and Hoorne are two central figures of a conflict commonly known as the Dutch Revolt. In his book Egmont da capo – eine mythogenetische Studie (Egmont da capo – a Mythogenetic Study), a revised version of his PhD thesis, Rittersma shows how one of them, Egmont, became mythical in stature, with meanings reaching well beyond the original event. By analyzing a large amount of sources from the reception of the Egmont mythos, the author gives a precise survey of how myths in general are constructed and how they create their own dynamic—a dynamic that can be based on the original history but need not.